A COMPARISON OF TESTING METHODS FOR DETERMINATION OF SPRAYED CONCRETE TENSILE STRENGTH - Martin Závacký (Acta Polytechnica CTU Proceedings)
Sprayed concrete is important construction material in tunnelling. Primary lining is essential in NATM where the sprayed concrete can be loaded by tension due to bending moments. The tension is common reason of failure because concrete has a relatively low tensile strength. The tensile strength is usually determined by splitting tensile test in laboratory. However, the results can be distorted because the specimen is not loaded by pure tension in this case. The paper compares results of concrete tensile strength determined by two methods: indirect by the splitting tensile test and direct by the modified tensile test.